Pengaruh Motivasi Kerja, Komunikasi Dan Disiplin Kerja Terhadap Kinerja Karyawan (Studi Pada UMKM Degan Jelly Queen Di Desa Wringinputih, Kecamatan Muncar, Kabupaten Banyuwangi) - Salamah, Ah-lam Umul Khoir; Djaelani, Abdul Kodir; Amin, Muhammad Sirojuddin (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to analyze and explain the influence of Work Motivation, Communication, and Work Discipline on Employee Performance (Study on UMKM Coconut Jelly QUEEN in Wringinputih Village, Muncar District, Banyuwangi Regency). The population in this study is 36 employees, all of which are used as research samples. Using multiple linear regression analysis, this study analyzes the influence simultaneously and partially. The results of the study showed simultaneously that work motivation, communication, and work discipline had an effect on employee performance. Partially showed the results that communication and work discipline had an effect on employee performance. Another interesting result in this study is that work motivation has no effect on employee performance, due to the lack of supervision and coaching from the leadership. Keywords: Work Motivation, Communication, Work Discipline and Employee Performance.